(untitled) (NUTA Journal, 2022)
This article deals with technological accessibility, its effects on women, and the reflection on women’s empowerment. Women need technology for the same reason as men. It supports women without bias. Global efforts have been made to empower women through income-generating activities saving their time and labor spent in the household economy. Technology supports women to empower them in many respects by saving their time and labor as well as shaping their ability and the infrastructure of their work. The main objective of this article is to access the role of technology in empowering women; findout the relationship between women and technology and find out the social transformation that led through technology. This article has applied textual review-based analysis as a methodology. This article claims that technology and women are indispensable parts and powerful tools and techniques for empowering women. The conclusion is a positive vibrant relationship between technology and women’s empowerment whichis drawn from empirics. The outcome is carried out through empirical evidence from different countries’ experiences and issues.The development of women’s friendly technology has led to miraculous changes in women’s lives which could contribute to saving their time and labor and thinking a minute for themselves and about the world. Innovation in technology is contributing to women’s empowerment and social transformation.